2004
DOI: 10.1111/j.0038-4941.2004.08502011.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Lives on the Wrong Side of the Environmental Tracks? Evidence from the EPA's Risk‐Screening Environmental Indicators Model*

Abstract: Objective. We analyze the social and economic correlates of air pollution exposure in U.S. cities. Methods. We combine 1990 Census block group data for urbanized areas with 1998 data on toxicity‐adjusted exposure to air pollution. Using a unique data set created as a byproduct of the EPA's Risk‐Screening Environmental Indicators Model, we improve on previous studies of environmental inequality in three ways. First, where previous studies focus on the proximity to point sources and the total mass of pollutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 12 publications
8
149
0
3
Order By: Relevance
“…Environmental justice studies based in the USA have also found a higher proportion of minorities near hazardous facilities (Ash and Fetter, 2004;Pastor et al, 2004), which supports the notion posited by Buzzelli and Jerrett (2004) that "environmental racism" may be a more appropriate term than environmental justice to describe disparities. This is despite the fact that residential segregation is not found to the same degree in Canadian urban areas as it is in the USA (Walks and Bourne, 2006).…”
Section: Inequitable Exposure To Toxic Air Pollutionsupporting
confidence: 64%
“…Environmental justice studies based in the USA have also found a higher proportion of minorities near hazardous facilities (Ash and Fetter, 2004;Pastor et al, 2004), which supports the notion posited by Buzzelli and Jerrett (2004) that "environmental racism" may be a more appropriate term than environmental justice to describe disparities. This is despite the fact that residential segregation is not found to the same degree in Canadian urban areas as it is in the USA (Walks and Bourne, 2006).…”
Section: Inequitable Exposure To Toxic Air Pollutionsupporting
confidence: 64%
“…Our findings emphasize the importance of taking into account the toxicity of the waste being emitted by these plants (Ash, and Fetter 2004;Brooks, and Sethi 1997;Neumann et al 1998;Sicotte, and Swanson 2007). Whereas prior work frequently views only the presence of a toxic waste site in a tract, or the raw number of pounds of waste being emitted, differential effects were found when taking into account the relative toxicity of the emitted waste.…”
Section: Discussionmentioning
confidence: 53%
“…One rare study attempting to tease out the causal direction between the placement of toxic sites and the presence of racial/ethnic minorities focused on tracts within the city of Los Angeles over three decades (Pastor et al 2001). This limited literature suggests an important need for further longitudinal studies.Our study addresses the following questions: 1) what is the relative proximity to toxic waste sites for minority groups over a ten year period from 1990 to 2000; 2) do neighborhoods with more highly educated residents experience less proximity to toxic waste sites; and 3) do these effects differ if we take into account the toxicity of the emitted wastes (Ash, and Fetter 2004;Brooks, and Sethi 1997;Neumann, Forman, and Rothlein 1998;Sicotte, and Swanson 2007). Beyond our longitudinal approach, we assess the impact of toxic sites on neighborhood Disproportionate toxicity proximity 6 residents by measuring the pounds of release weighted by a measure of its toxicity, and apportioning this value to a one-mile circle around the site rather than simply attributing it to the census tract in which the site is located (other studies using this approach include Bolin et al 2002;Mohai, and Saha 2006).…”
mentioning
confidence: 99%
“…Researchers have found income and poverty to be consistently associated with hazard presence in the expected direction: as environmental hazard presence increases, incomes decrease and poverty rates increase (Ash and Fetter, 2004;Been, 1994;Charkraborty and Armstrong, 1997;Derezinski et al, 2003;Downey, 2003;Hamilton, 1995;Krieg, 1995;Lester et al, 2001;McMaster et al, 1997;Mohai and Bryant, 1992;Morello-Frosch et al, 2001;Oakes et al, 1996;Ringquist, 1997;Stretesky and Hogan, 1998).…”
Section: Literature Reviewmentioning
confidence: 98%
“…1 Moreover, only two studies that I am aware of have attempted to explain why environmental racial inequality levels vary from one city or region of the country to another (Ash and Fetter, 2004;Brown et al, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%